PROSPECTIVE STUDY TO EXPLORE THE RELATIONSHIP BETWEEN DOSIMETRIC PATTERN AND QUALITY OF LIFE IN HEAD AND NECK CANCER PATIENTS TREATED BY IMRT - NANDA, TARUN; YASHVI; BHAMRA, HARTANYA; SHARMA, ANKUR; A., PRANAM (International Journal of Current Pharmaceutical Research, 2024)
Objective: This prospective study aimed to explore the relationship between dosimetric patterns and quality of life (QOL) outcomes in patients with head and neck cancer (HNC) treated with Intensity-Modulated Radiotherapy (IMRT). Methods: Conducted at the Department of Radiation Oncology, RNTMC, Udaipur, Rajasthan, from January to December 2023, this hospital-based observational study included 100 patients with histologically confirmed squamous cell carcinoma of the head and neck. Patients underwent IMRT with specific dosimetric parameters targeting various structures while assessing QOL using the EORTC QLQ-C30 and QLQ-HN-35 questionnaires at baseline, 3, and 6 mo post-treatment. Results: The study encompassed predominantly male patients (89%) with a mean age of 53.02±13.10 y. Tongue cancer was the most common site (38%), followed by oropharynx (16%) and buccal mucosa (14%). Dosimetric analysis revealed that higher mean doses to the left and right parotid glands and constrictor muscles were significantly associated with increased severity of symptoms, impacting QOL negatively. Notably, increased mean doses correlated with more severe issues related to pain, swallowing, sensory problems, speech, and social aspects of eating and contact. Conclusion: This study underscores the critical impact of dosimetric patterns on the QOL of HNC patients treated with IMRT. Optimizing dosimetric parameters to minimize exposure to critical structures like the parotid glands and constrictor muscles can potentially mitigate treatment-related toxicities, thus enhancing patients' QOL. Future strategies should focus on tailored radiation therapy plans to balance tumor control and preservation of QOL.